Meningkatkan Hasil Belajar Siswa Pada Materi Perubahan Bentuk Energi Melalui Model Cooperative Learning di Kelas III SDN 1 Sankanwangi Lebak Banten - Abun Sudiyana; Rifki Arif Nugraha; Ratna Dewi (Desanta Publisher, 2023)
ABSTRACT Based on the formulation, the problem regarding students' low understanding of changes in energy forms, then prompted the author to conduct research on how teachers' efforts to improve student learning outcomes about learning science in elementary school students. In this study the authors used the cooperative learning strategy. In this research methodology, the authors used Classroom Action Research with an observational flow to determine the extent to which students understood interest in reading in Indonesian lessons, especially about increasing interest in reading. To find out that everything the author does is implementing classroom learning, which consists of four stages, namely Planning (Action Planning), Acting (Implementation of Actions), Observing (Observation), and Reflecting (assessment/Evaluation stage). And the results of observations made by the teacher are good. Because most of the components that have been determined in the implementation of learning have been carried out properly. Research Results, From good learning outcomes, good results will also be obtained. The results of the research show that science learning through cooperative learning has increased. This can be seen through the first cycle/meeting I, students studying through only achieve an average value of 75.45. In cycle II there is an increase in students learning through through with an average score of 90.90. The average student activity in terms of seriousness and activeness in carrying out the tasks given by the teacher in cycle I was in the Good category and cycle II was in the very good category. Time This research was conducted from July 2023 to September 2023, a total of 22 students at SDN I Sankanwangi, Lebak Regency. Keywords: Learning Outcomes, Cooprative Learning, Changes in the Form of Puzzle Energy